Utilization Rate and Factors Associated with Non-Utilization of Non-Pneumatic Anti-Shock Garment in the Management of Obstetric Hemorrhage in Public Health Care Facilities of Northern Ethiopia: A Cross-Sectional Study - Desta AA; Berhane M; Woldearegay TW (Dove Medical Press, 2020)
Abraham Aregay Desta,1 Mentsegeba Berhane,2 Tewolde Wubayehu Woldearegay3 1Public Health Research, Tigray Health Research Institute, Mekelle, Tigray, Ethiopia; 2Maternal Care, Mekelle Hospital, Mekelle, Tigray, Ethiopia; 3Tigray Health Research Institute, Mekelle, Tigray, EthiopiaCorrespondence: Abraham Aregay DestaPublic Health Research, Tigray Health Research Institute, P.O. Box 1547, Mekelle, Tigray, EthiopiaEmail abaregaydesta@gmail.comBackground: Obstetric hemorrhage (OH) causes more than 25% of the maternal deaths across the world annually. A significant number of these deaths can essentially be prevented with a skilled birth attendant and having all-inclusive emergency obstetric care technologies. One of these promising technologies is to utilize non-pneumatic anti-shock garment (NASG). Despite this fact, there are limited studies on the utilization of NASG in Ethiopia.Objective: The aim of this study was to assess the utilization rate and factors associated with non-utilization of NASG in the management of obstetric hemorrhage in public healthcare facilities of Northern Ethiopia.Methods: An institution-based cross-sectional study was conducted from December 2017 to February 2018 involving 338 randomly selected healthcare providers working in the maternity healthcare facilities. Data were collected using pre-tested and self-administered questionnaires. Data were entered and analyzed using STATA version 14.0 statistical software package. The result was displayed using descriptive, bivariate, and multivariable logistic regression analysis to identify independent predictors of non-utilization of NASG at a P-value≤ 0.05.Results: About 121 (35.80%; 95% CI=30.68– 41.16%) of the health workers did not utilize NASG, and 217 (64.20%; 95% CI=58.84– 69.32%) utilized NASG. Being females, with adjusted odds ratio (AOR)=2.21 (95% CI=1.06– 4.63), use of NASG in previous works to manage OH, with AOR=0.1 (95% CI=0.02– 0.48), having perceived skill to use the garment in the facility, with AOR=0.10 (95% CI=0.01– 0.79), were significantly associated with the non-utilization of NASG.Conclusion: There was a lower rate of NASG utilization among the healthcare providers for the management of obstetric hemorrhage. Being a male care provider, having no experience of using NASG to manage PPH, and having perceived skill to use the garment in the healthcare facility were significantly associated factors for the non-utilization of the NASG. Due emphasis should be given to the utilization of NASG to manage obstetric hemorrhage by addressing the identified modifiable factors for non-utilization of NASG by healthcare workers.Keywords: maternal and child health, non-pneumatic anti-shock garment, Ethiopia